Synthesis, Characterization and Photocatalytic Application of TiO2, Nd3+, Cu2+ Masked Chitosan Nanocomposite - Yousefi, M.; Ghasemi, S. (Asian Journal of Chemistry, 2012)
Cu2+, Nd3+-Doped nanostructure TiO2-coated Nd3+ (TiO2/Nd3+) were prepared by sol-gel method. Titanium dioxide were synthesized by the sol-gel method using tetra n-butyl orthotitanate (TBT) as a precursor. The prepared nanoparticles characterized by XRD, SEM and TEM. The XRD showed that the major phase of nanocomposite is anatase. The morphology of the TiO2/Nd3+/ Cu2+/chitosan microsphere was investigated using SEM. The TEM shows that the size of TiO2/ Nd3+/Cu2+/chitosan was 8-10 nm. Moreover, particles shape were spherical. Acid red 151 removed photochemically by adding TiO2/Nd3+/Cu2+/chitosan nanoparticle and H2O2 in the presence of the UV radiation. The results show that the kinetics model reaction in presence of catalyst followed from pseudo-second order equation presented by Blanchard.